2016
DOI: 10.1093/mmy/myw105
|View full text |Cite
|
Sign up to set email alerts
|

Human primary myeloid dendritic cells interact with the opportunistic fungal pathogenAspergillus fumigatusvia the C-type lectin receptor Dectin-1

Abstract: Aspergillus fumigatus is an opportunistic fungal pathogen causing detrimental infections in immunocompromised individuals. Dendritic cells (DCs) are potent antigen-presenting cells and recognize the A. fumigatus cell wall component β-1,3 glucan via Dectin-1, followed by DC maturation and cytokine release. Here, we demonstrate that human primary myeloid DCs (mDCs) interact with different morphotypes of A. fumigatus. Dectin-1 is expressed on mDCs and is down-regulated after contact with A. fumigatus, indicating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 24 publications
2
11
0
Order By: Relevance
“…Plasma βDG levels positively correlated with the frequency of activated CD4 and CD8 T cells and plasma sCD14 and negatively correlated with Dectin-1 and NKp30 expression on monocytes and NK cells, respectively. Such relationships are supported by previous findings of βDG stimulation leading to monocyte and NK cell activation as well as IL-6 and IL-8 production via Dectin-1 and NKp30, respectively [34][35][36][37]. Our study showed there was an inverse correlation between βDG levels with Dectin-1 and NKp30 expression in PLWH, demonstrating that βDG Comparison of βDG with markers of bacterial translocation, gut damage, and HIV disease progression.…”
Section: Discussionsupporting
confidence: 91%
“…Plasma βDG levels positively correlated with the frequency of activated CD4 and CD8 T cells and plasma sCD14 and negatively correlated with Dectin-1 and NKp30 expression on monocytes and NK cells, respectively. Such relationships are supported by previous findings of βDG stimulation leading to monocyte and NK cell activation as well as IL-6 and IL-8 production via Dectin-1 and NKp30, respectively [34][35][36][37]. Our study showed there was an inverse correlation between βDG levels with Dectin-1 and NKp30 expression in PLWH, demonstrating that βDG Comparison of βDG with markers of bacterial translocation, gut damage, and HIV disease progression.…”
Section: Discussionsupporting
confidence: 91%
“…We hypothesize that downregulation of Dectin-1 exposure on human moDCs prevents severe and uncontrolled inflammatory reactions while on murine BMDCs, Dectin-1 expression is required for continuous ingestion and killing of the fungus. This is consistent with our previous data showing that anti-Dectin-1 antibody treatment of human moDCs as well as ex vivo myeloid DCs subsequently inhibited secretion of pro-inflammatory cytokines after contact with A. fumigatus, C. albicans , or zymosan ( 4 , 39 ). This is also consistent with the observation that naïve mice lacking Dectin-1 show reduced killing of conidia and a higher mortality rate than wild-type mice ( 40 ).…”
Section: Discussionsupporting
confidence: 93%
“…Based on criterion 2 (constitutive expression ≥ 50 RKPM), we identified a further 13 candidate receptors, of which six were differentially regulated (criterion 3). Without exception, all six genes were down-regulated upon stimulation with β-glucans, which could possibly be explained by a need to restrict de novo protein synthesis and duration of signalling to prevent over-stimulation (6063). Possibly, analysis of protein and/or gene expression at different time points could show up-regulation.…”
Section: Discussionmentioning
confidence: 99%